Antioxidant and antimicrobial activity of cuttlebone chitosan against Escherichia coli, Staphylococcus aureus and Candida albicans - Masnita Fatihah Md Zahir,; Rashidah Iberahim,; Nazlina Ibrahim,; Ruhaida Rusmin,; Noor Atikah Jailani,; Nurul Illiya Zafirah Zulkifli, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The discovery of new antibiotics for infectious diseases has become challenging due to the rise of antimicrobial resistance. Meanwhile, chitosan has been considerably used in many branches of research. It has been discovered to have some good benefits in medicals, pharmaceuticals, and food technologies. In this study, chitosan was prepared from the cuttlebone of Sepia sp. by chemical method and analyzed by using FT-IR spectrophotometer for the confirmed presence of its functional groups. There are three types of reactive functional groups in the chitosan which are the amino group and primary and secondary hydroxyl group attached to the C-2, C-3, and C-6 positions respectively. Chitosan has a high cationic property due to the presence of its amino group. The bacteriostatic activity of chitosan occurs due to its positive charge in acidic concentration that interacts with the negatively charged residue of carbohydrates, lipids, and proteins located on the cell surface of bacteria. The antioxidant activity was conducted using DPPH radical scavenging assay with a chitosan concentration ranging from 0.1 to 10 mg/mL and a hydrogen peroxide scavenging assay with a chitosan concentration ranging from 0.1 to 1.6 mg/mL. The antimicrobial activity of chitosan from cuttlebone was analyzed against two different bacterial strains (Escherichia coli & Staphylococcus aureus) and a fungal strain, Candida albicans by disc diffusion and minimum inhibitory concentration (MIC) method. The results show that through the DPPH radical assay, the scavenging activity was 59.7% at the concentration of chitosan at 10mg/mL, while through the hydrogen peroxide assay the scavenging activity was 56% at the concentration of chitosan at 1.6 mg/mL. Besides, this chitosan from Sepia sp. has concentration-dependent antimicrobial activity with higher antifungal activity compared to antibacterial activity against all tested organisms and may become a potential agent for antibiotic discovery.